Youth Consumptive Behavior at the Matahari Mall in Palopo City - Idham Irwansyah; Anastasia Astuti; Firdaus Suhaeb; Sopian Tamrin (Pinisi Business Administration Review, 2019)
This study aims to determine the consumptive behavior of adolescents at the Matahari Mall. This type of research is qualitative research. The technique of collecting observations, interviews and documentation data with the number of informants was 10 people who were determined intentionally, with the criteria of mall sun visitor informants aged between 14 to 18 years. With descriptive qualitative data analysis techniques through stages of reduction, display and conclusion, the technique of validating data is data triangulation. The conclusions of the study are as follows: the city in Palopo emphasizes tertiary needs rather than primary needs. b. The existence of the Mall has had an influence on adolescents, especially in changing patterns of behavior and changing the lifestyle of adolescents and society. c. factors that influence adolescent consumptive behavior are cultural factors, economic factors, social status factors, product factors, lifestyle factors and personal factors.